2020
DOI: 10.1039/d0ta06238c
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing pore and heteroatom utilization within N,P-co-doped polypyrrole-derived carbon nanotubes for high-performance supercapacitors

Abstract: Promoting the efficient utilization of both the pores and heteroatoms remains a highly challenging endeavor, yet is of crucial significance to enhance the specific capacitance and energy density of carbon-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…has also been assisted thoroughly to the various applied fields (Fig. 3), such as supercapacitors materials [18][19][20], solar cells [21][22][23], as battery electrode's [24,25], catalyst supports systems for proton exchange membrane fuel cells [26][27][28], and also to develop polymer nanocomposites for various applications [29][30][31] i.e. in drug delivery, bio-imaging [32][33][34], medicinal biology [35][36][37][38], aerospace [39,40], new age weapon technology [41,42] etc.…”
Section: Introductionmentioning
confidence: 99%
“…has also been assisted thoroughly to the various applied fields (Fig. 3), such as supercapacitors materials [18][19][20], solar cells [21][22][23], as battery electrode's [24,25], catalyst supports systems for proton exchange membrane fuel cells [26][27][28], and also to develop polymer nanocomposites for various applications [29][30][31] i.e. in drug delivery, bio-imaging [32][33][34], medicinal biology [35][36][37][38], aerospace [39,40], new age weapon technology [41,42] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3a displays the comparative CV curves of NSC, NCuSC, and NCoSC at 30 mV s −1 scan rate over the working potential window of −0.1 to 0.4 V. The CV curves showed that the integrated area of NCoSC was larger than the other two implying the best electrochemical performance of the NCoSC electrode. The CV curves also showed a pair of redox peaks in all the electrodes indicating that the main charge storage characteristics were dominated by the reversible Faradic redox reaction of metal sulfides [2,4,[33][34][35]. CV curves also suggested that the NCoSC and NCuSC electrodes showed pure battery-like behavior.…”
Section: Electrochemical Characterization Of Electrodesmentioning
confidence: 91%
“…Higher retention of capacitance of NCoSC is attributed to the synergistic effect between the transition metals carbon coating. Improvement in electrical conductivity is attributed to the interconnected network structure of NCoSC electrode, contributing to achieving higher electrochemical properties [4][5][6]12,32,38]. EIS is a principal method to measure the internal resistance and ion diffusion properties of the materials.…”
Section: Electrochemical Characterization Of Electrodesmentioning
confidence: 99%
See 2 more Smart Citations